2009
DOI: 10.1021/ja903790y
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Himandrine

Abstract: We describe the first total synthesis of (−)-himandrine, a member of the class II galbulimima alkaloids. Noteworthy features of this chemistry include a diastereoselective Diels-Alder reaction in the rapid synthesis of the tricycle ABC-ring system in enantiomerically enriched form, the use of a formal [3+3] annulation strategy to secure the CDE-ring system with complete diastereoselection, and successful implementation of our biogenetically inspired oxidative spirocyclization of an advanced intermediate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 29 publications
0
48
0
1
Order By: Relevance
“…In the synthesis of (−)-galbulimima alkaloid, the Movassaghi research group reported the use of copper-inspired coupling of vinyl bromide and oxazolidinone as one of its key intermediate steps [35]. A similar strategy was also employed in the synthesis of himandrine alkaloid [36]. Bergman et al also reported the use of copper catalyzed amidation reactions as one of its key strategies in the synthesis of the alkaloid vasicoline [37].…”
Section: Introductionmentioning
confidence: 99%
“…In the synthesis of (−)-galbulimima alkaloid, the Movassaghi research group reported the use of copper-inspired coupling of vinyl bromide and oxazolidinone as one of its key intermediate steps [35]. A similar strategy was also employed in the synthesis of himandrine alkaloid [36]. Bergman et al also reported the use of copper catalyzed amidation reactions as one of its key strategies in the synthesis of the alkaloid vasicoline [37].…”
Section: Introductionmentioning
confidence: 99%
“…The latter can be stabilized by an appendant enone (or enoate) and therefore has potential to trigger subsequent chemical reactions with appropriate substrates. Polycyclic dihydrofuran skeletons are widespread among various natural products of important biological activities [10] and also serve as very useful precursors for the construction of molecular complexity such as (À)-himandrine [11] and cyathin A 3 . [12] At present, however, the formation of the bicyclic dihydrofuran framework generally involves building a second five-or six-membered ring onto a preformed dihydrofuran moiety in several steps, which dramatically weakens the overall efficiency.…”
mentioning
confidence: 99%
“…Inspired by this putative biosynthetic pathway, the authors achieved the total synthesis of both alkaloids of Class II (himandrine) [10] and Class III (Galbulimima alkaloid 13 or GB 13) [7]. During these investigations, they obtained exciting results that support their hypothesis.…”
Section: Alkaloids Of Class Imentioning
confidence: 99%